The effect of multimedia on enhancing mathematical problem-solving skills among seventh grade students in North Eastern province, Sultanate of Oman - تأثٌر الوسائط المتعددة على تعزٌز مهارات حل المشكلات الرياضية بين طلا الصف السابع في مقاطعة شمال الشرقية بسلطنة عمان - Humaid Al Jabri, Isehaq Humaid Said; Sahrir, Muhammad Sabri (OCERINT International Organization Center of Academic Research, 2020)
This quantitative, analytical study discusses the impact of multimedia on enhancing mathematical problem solving skills among seventh graders in the Northeast District. Where the problem arose in that research and studies indicated the low level of performance of seventh-graders in solving mathematical problems, and that the teaching method used is dominated by speech and instruction on the part of the teacher, and memorization and memorization on the part of the student, without interest in improving the level of his higher thinking capabilities, including the ability to Mathematical problem solving. Therefore, the study aims to discuss the impact of multimedia on enhancing mathematical problem-solving skills among seventh graders, and to know the suggestions of teachers and specialists in developing the multimedia program. The researcher used the descriptive approach and the semi-experimental approach to a sample of students of (153) students for mathematics. The study tools included; the achievement test in the skills of solving the pre and post mathematical problems of the control and experimental group, as well as a motivational measure in mathematics. The sample was divided into a control group (77) students, and an experimental group (76) students. The results showed that there was a statistically significant difference at the significance level (0.05) between the mean scores of the pre and post measurements of the experimental group students, which were studied according to the multimedia program on the mathematical problem-solving test for mathematics course. And the presence of a statistically significant difference at the significance level (0.05) between the mean scores of the experimental group students and the students of the control group on the problem-solving test.